Análise do diagnóstico de enfermagem disposição para letramento em saúde melhorado em portadores de diabetes Mellitus Tipo II - ALMEIDA, Jocelha Maria Costa de (2022)
Health literacy (HL) is recognized as an effective mechanism in self-care, as it performs important health outcomes, especially in chronic conditions, such as type 2 diabetes mellitus (DM2) . This study aimed to analyze the nursing diagnosis (ND) readiness for improved health literacy in patients with DM2. It was organized into two chapters: 1) integrative review - health literacy in patients with DM2 on an outpatient basis; 2) nursing diagnosis readiness for improved health literacy in patients with DM2. In the first chapter, the selection of works published in virtual libraries and databases was carried out, which resulted in 7 international articles: two in Europe, two in Asia, one in Oceania, one in North America and one in Africa. It was concluded the absence of this ND in the studies and the SL when present is related to the level of knowledge, income and age and its absence shows harm to patients. In the second, there is the analysis of this ND in patients with DM2. Analytical, cross-sectional, quantitative study based on the database of the Group of Studies and Research in Nursing in Health Promotion and Clinical-Surgical Nursing (GEPEPSEC) tabulated in an Excel database. The present study evaluated the diagnostic accuracy based on latent class analysis adjusted for sensitivity, specificity and posterior probabilities. The association of the nursing diagnosis and the sociodemographic, clinical and risk factors variables were performed through logistic regression analysis. Most were between 60 and 79 years old, female, coming from São Luís - MA, urban area, married or stable union, own home, low education, Catholic, retired/pensioner/benefit and family income of one to two salaries -minimum Regarding the clinical factors, we highlight the use of oral hypoglycemic agents, free receipt of medication, absence of difficulties regarding the use and non following of the diet. The most prevalent risk factors were family history of DM2, systemic arterial hypertension, hypercholesterolemia, previous obesity, frequent use of alcohol and smoking. The diagnosis readiness for improved health literacy was present in 55.23% of the sample. The defining characteristic that best predicts this diagnosis is: it expresses a desire to improve communication about health with professionals. Significant associations: being from the interior of the state, living in a rented house, having higher education, being asymptomatic when he discovered the disease and having previous obesity, while performing the diagnosis of DM2 through the symptoms of the disease and not through routine exams are less likely to manifest the diagnosis in question. It is concluded that this diagnosis is prevalent in patients with DM2 and the DC referring to the process of communication with health professionals is the most sensitive to infer its occurrence in this clientele. In addition, understanding the diagnostic profile from the perspective of health literacy can contribute to the implementation of interventions that can improve the quality of nursing care.